(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The correct formation of knowledge, lexical, grammatical, and pronunciation concepts in the educational process, the correct content of the system of knowledge, self-control skills in the student’s mind is the result of innovative pedagogical technologies. is a component. Currently, the most effective teaching methods in the educational process, which are guaranteed to achieve the goals set by teachers and pedagogues, form the basis for students to think independently, make independent decisions, solve their problems, and get out of various situations without difficulty. such teaching methods capable of being prepared are the most advanced features of pedagogical technology.